2011
DOI: 10.1007/s00726-011-1152-3
|View full text |Cite
|
Sign up to set email alerts
|

SAR study of tyrosine–chlorambucil hybrid regioisomers; synthesis and biological evaluation against breast cancer cell lines

Abstract: Amino acids were transformed and coupled to chlorambucil, a well-known chemotherapeutic agent, in an attempt to create new anticancer drugs with selectivity for breast cancer cells. Among the amino acids available, tyrosine was selected to act as an estrogenic ligand. It is hypothesized that tyrosine, which shows some structural similitude with estradiol, could possibly mimic the natural hormone and, subsequently, bind to the estrogen receptor. In this exploratory study, several tyrosine-drug conjugates have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
(19 reference statements)
0
15
0
Order By: Relevance
“…Molecular modeling study indicated that the phenol group of tyrosine also interact with the estrogen receptor binding site in the same manner as the A-ring phenol of estradiol. Therefore, the tyrosine was modified to mimic the structure of estradiol (Muthyala et al, 2003; Descoteaux et al, 2012b). Tyrosinamide, combined tyrosine with hydroxyaniline, was proved to be structurally similar to estradiol.…”
Section: Nitrogen Mustard Based Hybridsmentioning
confidence: 99%
“…Molecular modeling study indicated that the phenol group of tyrosine also interact with the estrogen receptor binding site in the same manner as the A-ring phenol of estradiol. Therefore, the tyrosine was modified to mimic the structure of estradiol (Muthyala et al, 2003; Descoteaux et al, 2012b). Tyrosinamide, combined tyrosine with hydroxyaniline, was proved to be structurally similar to estradiol.…”
Section: Nitrogen Mustard Based Hybridsmentioning
confidence: 99%
“…All compounds with tyrosine showed higher cytotoxicity than pure chlorambucil. Compared to the other regioisomers, the m -tyrosine-chlorambucil compound showed greater cytotoxicity and it was also slightly more specific for hormone-dependent cancer cells, probably due to closer similarity to estradiol [53]. …”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%
“…4). 108 Novel plumbagin hydrazonates were prepared, structurally characterized and evaluated for anti-proliferative activity against the BC cell lines. Compounds 121 and 122 were especially promising against triple negative MDA-MB-231 (IC 50 values 1.9 and 2.1 mM, respectively) and MDA-MB-468 BC cell lines via inhibiting NF-B expression (Fig.…”
Section: The Miscellaneous Functional Groups Of Organic Compoundsmentioning
confidence: 99%